ECHINOCANDINS VERSUS DATED ANTIFUNGALS IN COMBINATION AGAINST OPPORTUNISTIC MYCOTIC INFECTIONS - Narwal, Mrridula Dangi; Balhara, Meenakshi; Chaudhary, Renu; Ak, Chhillar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Scientific and clinical reports globally demonstrated that the opportunistic mycotic infections are at major risk to the human fitness. In past few decades, development of resistance in microbes to existing antifungals, has emphasized on the search of new antimycotic drugs. As a matter of fact "echinocandins" are new categories of broad-spectrum antifungal enlighten a hope in this direction. Echinocandins are bulky lipopeptides that inhibits the production of Î²-[1,3]-glucan "a major constituent of fungal cell wall" which ultimately leads to the death of fungal pathogens. In vitro as well as in vivo published reports have demonstrated that the echinocandins exhibit fungicidal activity against most Candida spp while fungistatic against Aspergillus spp and exclusively found to be more effective when tested in combination with polyenes/azoles. Present article is an expert views on the recent and historical literature available on the antifungal therapies with accessing their impact on the human health. Emphasis is given on the utility of the echinocandins as potential antifungal agent by discussing recent examples of clinical and laboratory studies including the use of improved proteomics approaches to know a bit more about the interaction of human host and fungal pathogens.